Proceedings of SAE-China Congress 2015: Selected Papers - SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
These proceedings gather outstanding papers submitted to the 2015 SAE-China Congress, the majority of which are from China, the biggest car maker as well as most dynamic car market in the world. The book covers a wide range of automotive topics, presenting the latest technical achievements in the industry. Many of the approaches presented can help technicians to solve the practical problems that most affect their daily work.
Keywords: Automotive engineering; Transportation engineering; Traffic engineering; Engineering design; Electrical engineering; Automotive Engineering; Transportation Technology and Traffic Engineering; Engineering Design; Electrical and Electronic Engineering